IMPLEMENTATION OF COMMON SENSE IN DIFFERENTIAL LEARNING IN ELEMENTARY SCHOOL STUDENTS - Muhammad Yusuf; Akmaluddin; Siti Mayang Sari; Mhd. Syafii (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The application of common sense in differentiated learning is an approach that aims to present a more meaningful and inclusive learning experience for students with different learning styles, speeds, and needs. implementation of the concept of common sense in the context of differentiated learning. Common sense, as an individual's intuitive knowledge in everyday situations, becomes a valuable tool in helping students understand concepts through analogies and illustrations that are relevant to real life. Through the application of common sense, teachers can design more in-depth learning experiences by connecting learning concepts with student experiences. Practical strategies, such as using real-world situations in learning content, applying case studies, and using technology to present material more concretely. In addition, the importance of creating an inclusive and responsive learning environment to student differences is emphasized in this article. Through the implementation of common sense in differentiated learning, teachers can provide learning experiences that are more connected to students' realities, stimulate analytical thinking, and create learning experiences that are more diverse and meaningful for each student.